The effect of external compressive loads on the cycle lifetime of lithium-ion pouch cells. (October 2017) - Barai, Anup; Tangirala, Ravichandra; Uddin, Kotub; Chevalier, Julie; Guo, Yue; McGordon, Andrew; Jennings, Paul
Highlights: External pressure increases battery resistance, which continues to grow when cycled. Capacity fade is reduced when cycled under pressure. Pressure increases with cycling. Under pressure, separator creep happens which leads to resistance growth. Wettability of the electrodes increases when external pressure is applied. Abstract: In application, lithium-ion pouch-format cells undergo expansion during cycling. To prevent contact loss between battery pack components and delamination and deformation during battery operation, compressive pressure is applied to cells in automotive battery modules/packs by way of rigid cell housing within the modules. In this paper, the impact of such compressive pressure on battery degradation is studied. Samples of commercial, 15 Ah LiNiMnCoO2 /Graphite electrode pouch-type cells were cycled 1200 times under atmospheric, 5 psi and 15 psi compressive loads. After 1200 cycles, the capacity fade for 0, 5 and 15 psi loads was11.0%, 8.8% and 8.4%, respectively; the corresponding power fade was found to be 7.5%, 39% and 18%, respectively, indicating power fade peaks between 0 and 15psi. This contrasting behaviour is related to the wettability increase and separator creep within the cell after compressive load is applied. The opposing capacity fade and power fade results require consideration from automotive battery engineers at the design stage of modules and packs. In addition to capacity fade and power fade results, the study identified the evolution of compressive pressures over multiple cycles, showing that pressure increases with cycling.